2019
DOI: 10.1007/s10989-019-09888-2
|View full text |Cite
|
Sign up to set email alerts
|

Smp76, a Scorpine-Like Peptide Isolated from the Venom of the Scorpion Scorpio maurus palmatus, with a Potent Antiviral Activity Against Hepatitis C Virus and Dengue Virus

Abstract: Growing global viral infections have been a serious public health problem in recent years. This current situation emphasizes the importance of developing more therapeutic antiviral compounds. Hepatitis C virus (HCV) and dengue virus (DENV) belong to the Flaviviridae family and are an increasing global health threat. Our previous study reported that the crude venom of Scorpio maurus palmatus possessed anti-HCV and anti-DENV activities in vitro. We report here the characterization of a natural antiviral peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Scorpion venoms are cocktails of diverse biologically active compounds (see, inter alia, Rodriguez de la Vega and Possani, 2005;Rodriguez de la Vega et al 2010;Cao et al 2014;Abdel-Rahman et al 2015;Cid-Uribe et al 2018;Kazemi and Sabatier, 2019) and provide a rich source of AMPs (for reviews see Harrison et al 2014;Wang and Wang, 2016;El-Bitar et al 2019). Abdel-Rahman et al (2013) identified two novel amphipathic cationic AMPs (Smp43 and Smp24) through cDNA sequencing of the venom gland of the Egyptian scorpion Scorpio maurus palmatus.…”
Section: Introductionmentioning
confidence: 99%
“…Scorpion venoms are cocktails of diverse biologically active compounds (see, inter alia, Rodriguez de la Vega and Possani, 2005;Rodriguez de la Vega et al 2010;Cao et al 2014;Abdel-Rahman et al 2015;Cid-Uribe et al 2018;Kazemi and Sabatier, 2019) and provide a rich source of AMPs (for reviews see Harrison et al 2014;Wang and Wang, 2016;El-Bitar et al 2019). Abdel-Rahman et al (2013) identified two novel amphipathic cationic AMPs (Smp43 and Smp24) through cDNA sequencing of the venom gland of the Egyptian scorpion Scorpio maurus palmatus.…”
Section: Introductionmentioning
confidence: 99%
“…BmKDfsin3 is a scorpion defensing peptide developed from M. martenssi Karsch. It consists of 38 amino acid residues, with six cysteine residues forming three pairs of disulfide bonds[24]. The IC 50 is around 3.35 μM.…”
mentioning
confidence: 99%
“…The peptides of scorpion venom exhibit various biological and pharmacological activities (Abdel-Rahman et al, 2015;Cheng et al, 2020;El-Bitar et al, 2019;Elrayess et al, 2019;Harrison et al, 2014;Zeng, Gerardo Corzo, & Hahin, 2005). Peptides are the most abundant structures of scorpion venom and responsible for the neurotoxic as well as cytotoxic effects associated with scorpion sting (Jungo & Bairoch, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the animal venoms (such as snake, marine conus, frog, spider, and scorpion toxins) are considered as one of the main sources for the discovery of these compounds (with high selectivity and therapeutic index; Rajendra, Armugam, & Jeyaseelan, 2004;Altawil, Abdel-Rahman, El-Naggar, El-Khayat, & Abdel-Daim, 2015;Safavi-Hemami, Brogan, & Olivera, 2019). Scorpion venom is a rich source of several biologically active molecules (Abdel-Rahman, Harrison, & Strong, 2015;Harrison, Abdel-Rahman, Strong, Tawfik, & Miller, 2016) with various pharmacological properties including antitumor (Elrayess et al, 2019;Ghosh, Roy, Nandi, & Mukhopadhyay, 2019;Mamelak, 2011), analgesic (Chen & Ji, 2002;Shao et al, 2007), antiepileptic (Wang et al, 2001;Yu, Zhang, Wang, & Liu, 1992), and antimicrobial (El-Bitar et al, 2019;Harrison, Abdel-Rahman, Miller, & Strong, 2014;Harrison et al, 2016) activities. The whole body of Chinese scorpion Buthus martensi Karsch (BmK) or its venom has been found to be effective in treating certain neurological disorders (such as hemiplegia, facial paralysis, apoplexy, cerebral palsy, and epilepsy), nerve soothing, and as pain killers (especially pains induced by rheumatism and meningitis; Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%